Associations between workplace affiliation and phlebotomy practices regarding patient identification and test request handling practices in primary healthcare centres: a multilevel model approach. Issue 1 (June 2015) - Nilsson, Karin; Juthberg, Christina; Söderberg, Johan; Bölenius, Karin; Grankvist, Kjell; Brulin, Christine; Lindkvist, Marie
Abstract Background Clinical practice guidelines aim to enhance patient safety by reducing inappropriate variations in practice. Despite considerable efforts to enhance the use of clinical practice guidelines, adherence is often suboptimal. We investigated to what extent workplace affiliation explains variation of self-reported adherence to venous blood specimen collection regarding patient identification and test request handling practices, taking into consideration other primary healthcare centre and individual phlebotomist characteristics. Methods Data were collected through a questionnaire survey of 164 phlebotomy staff from 25 primary healthcare centres in northern Sweden. To prevent the impact of a large-scale education intervention in 2008, only baseline data, collected over a 3-month period in 2006–2007, were used and subjected to descriptive statistics and multilevel logistic analyses. Results In two patient identification outcomes, stable high median odds ratios (MOR) were found in both the empty model, and in the adjusted full model including both individual and workplace factors. Our findings suggest that variances among phlebotomy staff can be largely explained by primary healthcare centre affiliation also when individual and workplace demographic characteristics were taken in consideration. Analyses showed phlebotomy staff at medium and large primary healthcare centres to be more likely to adhere to guidelines than staff at small centres. Furthermore, staff employed shorter time at worksite to be more likely to adhere than staff employed longer. Finally, staff performing phlebotomy every week or less were more likely to adhere than staff performing phlebotomy on a daily basis. Conclusion Workplace affiliation largely explains variances in self-reported adherence to venous blood specimen collection guidelines for patient identification and test request handling practices among phlebotomy staff. Characteristics of the workplace, as well as of the individual phlebotomist, need to be identified in order to design strategies to improve clinical practice in this and other areas.